Casuarina Plantation Technique in the Madras Province - Raghavan, M. S. (Indian Forester, 1947)
Attention is concentrated only on Casuarina plantation technique in a few divisions which have been selected as typical. Therefore, it has been neeessary to omit mention of several division in the interests of brevity, though it is known that valuable work is done in them. The justification is that the Work can be classified under one of the types chosen. The sources of information are mentioned. It is stated that only typical areas, representing different types have been included in the report. The variations in climatic and soil conditions under which casuarina can be grown have been indicated. The interaction of casuarina growth and soil moisture are mentioned. The season for seed collection, the method of collection, the agency of collection, and the preservation of seed have been stated. It has been stated that very tail plants have sometimes disproportionately shallow and insufficient root systems. The variation in growing seasons between dry and moist localities is also indicated. The uncertainty of natural regeneration by direct seed fall, by coppicing and by layering, and the consequent necessity for artificial regeneration have been mentioned. Artificial regeneration is either by selecting barren sandy coastal areas, or by clearfelling and burning interior areas with some growth, and entire transplanting with suitable soil preparation, of tall nursery-raised plants in pits. The rotation for Casuarina plantations in the province varies from six to ten years, but in one division the district forest officer is expected to use his discretion after ten years and to extend the rotation up to fifteen years if necessary. The preparation of the planting site, including felling regrowth, uprooting stumps and roots, heaping, burning, alignment, staking, pitting, and fencing have been discussed. Details of nursery technique have also been given. The best espacement, the best size of transplants, the best season for transplanting, and the actual method of transplanting have been defined. The need for watering, the number of years when watering is necessary. The periodicity of watering, and the quantity of water required, have all been reported on. In general planting entire nursery raised six months old transp1ants, about two feet in height at an espacement of 7 by feet in prepared one foot cube its in June or July at the beginning (Of the south west monsoon, followed by adequate watertng on non-rainy days for a period .Of one to three years (except under the dry technique of Mysore) under a rotation of seven to ten years have been favoured. Post plantation operations such as soil aeration, weeding, climber cutting, pruning, and replacement of casualties, have been described. The advantage of horse gram kumri has been considered. The necessity and degree of thinning hall been discussed. It is considered that for fuel plantaltions on a short rotation, with aft initial espacement of 7 X 7 ft., thinning is unnecessary. External dangers from animals, insects, fire, and fungus have been discussed and remedies suggested. As the yleid varies very considerably, no details have been furnished.